Technical Analysis of a Non-Globally Integrated Stock Index - Gallegos-Erazo, Franklin Antonio; Gallardo-Cornejo, Ana María (Revista Venezolana de Gerencia, 2025)
This study examines the Ecuadorian stock market index, ECUINDEX, a market that is not integrated into international financial markets, unlike others in Latin America. The objective was to determine if graphical technical analysis can describe the price behavior of the ECUINDEX, testing the weak-form efficient market hypothesis. Market stationarity was evaluated to identify suitable volatility indicators. A mixed-methods approach was applied, combining quantitative tests (Boxplot and Dickey-Fuller) with qualitative analyses (graphical observation of prices and TEMA, RVI, and MA indicators). Monthly and daily closing price data of the ECUINDEX from 2013 to 2023 were analyzed, obtained from the Quito Stock Exchange through Investing. The results reveal that the ECUINDEX is non-stationary and that technical analysis consistently describes momentum, price direction changes, and market turns, highlighting the usefulness of technical indicators for understanding price trends and market inefficiencies.